2021
DOI: 10.3390/biomedicines9060667
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles of Mesenchymal Stem Cells: Therapeutic Properties Discovered with Extraordinary Success

Abstract: Mesenchymal stem cells (MSCs), the cells distributed in the stromas of the body, are known for various properties including replication, the potential of various differentiations, the immune-related processes including inflammation. About two decades ago, these cells were shown to play relevant roles in the therapy of numerous diseases, dependent on their immune regulation and their release of cytokines and growth factors, with ensuing activation of favorable enzymes and processes. Such discovery induced great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 113 publications
(188 reference statements)
0
43
0
Order By: Relevance
“…Modulation of adipose-derived MSCs with lipopolysaccharide increased the levels of the tumor necrosis factor alpha (TNF-α) and IL-6 and increased the regenerative profile of the secretome [ 83 ]. Releases by MSCs vesicles are easy to collect, and their therapeutic possibilities have also been analyzed [ 11 , 17 , 84 , 85 ]. A vesicle including EXs is usually isolated from stem cells according to the standard protocol.…”
Section: Secretome Of Dental Pulp Mscs and Their Biological Effectmentioning
confidence: 99%
“…Modulation of adipose-derived MSCs with lipopolysaccharide increased the levels of the tumor necrosis factor alpha (TNF-α) and IL-6 and increased the regenerative profile of the secretome [ 83 ]. Releases by MSCs vesicles are easy to collect, and their therapeutic possibilities have also been analyzed [ 11 , 17 , 84 , 85 ]. A vesicle including EXs is usually isolated from stem cells according to the standard protocol.…”
Section: Secretome Of Dental Pulp Mscs and Their Biological Effectmentioning
confidence: 99%
“…As an example, mesenchymal stem cell (MSC) based cell therapies (from whom a large fraction of EVs potential drug products are derived) can hardly be explained by one specific pathway, and is now considered to be the result of a multifactorial effect involving both IDO-1 [115], PGE2, Nitric oxide [116], TGF-β1, IL-10, VEGF, HGF, mitochondrial transfer [117], etc. It is therefore very likely that MSC-EVs would also benefit from this pleiotropic effect as MSC-EVs are now reported to be the mediator of MSC therapeutic effect [118]. Some teams either tried to inhibit [3,6,7,[119][120][121][122] or activate particular pathways [4] that were expected to be involved in the MSC-EV mechanism of action and have shown that in both cases the results were not unequivocal, each pathway having been only responsible for a fraction of the effect.…”
Section: So What May Be "The" Ev Mechanism Of Action?mentioning
confidence: 99%
“…Furthermore, the potential of COVID-19 treatment can be improved by modifying the extracellular vesicles of MSCs (Ref. 109).…”
Section: Immunotherapy Of Covid-19mentioning
confidence: 99%